2014
DOI: 10.1902/jop.2013.130230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Periodontitis on Serum and Gingival Crevicular Fluid Oxidant and Antioxidant Status in Patients With Familial Mediterranean Fever Before and After Periodontal Treatment

Abstract: The results of the present study show that patients with FMF-CP displayed reduced oxidative stress and increased antioxidant status compared with those in the CP and HC groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 48 publications
4
37
1
2
Order By: Relevance
“…According to our results, patients with FMF had stronger clinical periodontal parameters than those of systemically healthy controls. Only four studies to date have introduced clinical periodontal parameters to analyze patients with FMF without amyloidosis . Although our results are similar to those studies that display increased gingival index values in patients with FMF without amyloidosis, it has also been reported that patients with FMF have significantly lower PD and CAL values than those of the control group .…”
Section: Discussionsupporting
confidence: 88%
“…According to our results, patients with FMF had stronger clinical periodontal parameters than those of systemically healthy controls. Only four studies to date have introduced clinical periodontal parameters to analyze patients with FMF without amyloidosis . Although our results are similar to those studies that display increased gingival index values in patients with FMF without amyloidosis, it has also been reported that patients with FMF have significantly lower PD and CAL values than those of the control group .…”
Section: Discussionsupporting
confidence: 88%
“…The search strategy yielded 3,199 studies, but just 20 fulfilled the inclusion criteria (Akpinar, Toker, Ozdemir, Bostanci, & Aydin, ; Bostanci, Toker, Senel, Ozdemir, & Aydin, ; Chaudhary, Gowda, Mehta, & Kumar, ; Cifcibasi et al., ; Dede, Ozden, & Avcı, ; Grant, Brock, Matthews, & Chapple, ; Guentsch et al., ; Hendek, Erdemir, Kisa, & Ozcan, ; Koromantzos et al., ; Kurgan et al., ; Marcaccini et al., ; Mizuno et al., ; Muthuraj et al., ; Novakovic et al., ; Önder et al., ; Patel, Rao, & Pradeep, ; Singh, Chander Narula, Kumar Sharma, Tewari, & Kumar Sehgal, ; Tamaki, Tomofuji, Ekuni, Yamanaka, & Morita, ; Toker, Akpınar, Aydın, & Poyraz, ; Wei, Zhang, Wang, Yang, & Chen, ). Figure summarizes the flow chart of the inclusion process, and the reasons for exclusions are expressed in Supporting Information Table .…”
Section: Resultsmentioning
confidence: 99%
“…Figure summarizes the flow chart of the inclusion process, and the reasons for exclusions are expressed in Supporting Information Table . The majority of the included studies were non‐RCTs (Akpinar et al., ; Bostanci et al., ; Cifcibasi et al., ; Dede et al., ; Grant et al., ; Guentsch et al., ; Hendek et al., ; Kurgan et al., ; Marcaccini et al., ; Muthuraj et al., ; Önder et al., ; Patel et al., ; Singh et al., ; Tamaki et al., ; Toker et al., ; Wei et al., ). Four studies were RCTs (Chaudhary et al., ; Koromantzos et al., ; Mizuno et al., ; Novakovic et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…29 Scaling and root planing is also capable of decreasing the total oxidant status in the gingival crevicular fluid and improving the antioxidant levels in patients with chronic periodontitis. 26,30 Therefore, periodontal diseases and reduced antioxidant levels seem to be associated with one another, leading to increased oxidative damages in the oral environment. This systematic review assessed the effect of antioxidant agents as complimentary to periodontal therapy in terms of oxidative stress/antioxidants.…”
Section: Introductionmentioning
confidence: 99%